The effects of Moringa peregrina seed meal, autoclaving, and/or exogenous enzyme cocktail on performance, carcass traits, meat quality, and blood lipids of broilers - Al-Harthi, Mohammed A.; Attia, Youssef A.; Elgandy, Mohamed F.; Bovera, Fulvia (Frontiers in Veterinary Science, 2023)
The effects of Moringa peregrina seed meal (MPSM), autoclaving, and/or enzyme cocktail addition on performance, profitability, carcass traits, meat quality, and blood lipids of broilers between 1-35 d of age were investigated. Seven experimental diets were employed: the control 0% MPSM, 10% raw MPSM, 10% autoclaved MPSM (at a temperature of 120 ºC and 1 kg/cm2 pressure for 30 min), 10% raw MPSM supplemented with enzymes at 0.1 or 0.2 g/kg feed, and 10% autoclaved MPSM supplemented with the same previous enzymes and doses. Each diet was fed to 8 replicates with 5 broilers in each. At the end of the experiment, 3 broilers from each replicate were randomly chosen to determine carcass traits, meat quality, and blood lipids. Findings at 35 d of age indicated that all 10% raw MPSM treatments with or without enzymes addition impaired growth, feed conversion (FCR), and profitability (P < 0.05), but increased feed intake (P < 0.05) and did not affect mortality when compared with the control group. The 10% autoclaved MPSM treatments with or without enzymes addition increased feed intake (P < 0.05) when compared with the control group, inducing growth equal to the control group (P > 0.05), and improving FCR and profitability. Enzymes addition to raw MPSM did not produce positive effects (P < 0.05), and no additive effect was observed when autoclaving and enzymes addition were combined (P > 0.05) as compared to the autoclaving group. Carcass traits, meat quality, and blood lipids were not significantly affected by MPSM, autoclaving, and enzymes addition. However, intestine, cecum, and gizzard percentages increased (P < 0.05) with all 10% raw MPSM treatments, while all 10% autoclaved MPSM treatments could return these values (P > 0.05) to the control group, except with gizzard, which exhibited less improvement. Additionally, all autoclaved groups had lower meat pH measured 24 h postmortem (P < 0.05) compared to the control group. In conclusion, autoclaved MPSM can be included in broilers’ diets at a 10% level without negative effects on performance, carcass traits, meat quality, and blood lipids. This indicates that autoclaving alone is adequate.